De- versus Re-industrialisation: Is Structural Change Reversible? - Michael Peneder; Gerhard Streicher (Austrian Institute of Economic Research (WIFO), 2016)
We investigate the causes of de-industrialisation and potential for re-industrialisation. Using WIOD data and introducing new measures of "induced value added chains", we directly relate a sector's income share to the net value added flows as induced by domestic and foreign final demand. This method identifies the declining share of manufacturing in domestic expenditures on final demand to be the main cause of de-industrialisation. International trade has a limited impact, though differences in comparative advantage between countries do matter. In addition, the strong decline of relative prices in manufacturing points to an interesting policy paradox: precisely if successful in raising competitiveness and hence productivity growth of manufacturing, they also further its global decline of relative prices. Contrary to the stated objective of re-industrialisation, meaningful industrial policies will accelerate de-industrialisation in the global economy. To raise the income share of manufacturing, policies must target, e.g., competition and productivity growth in services.
Keywords: 330; Industrial policy; de-industrialisation; global value chains; input-output analysis; WIOD